SPE Annual Technical Conference and Exhibition 1990
DOI: 10.2118/20421-ms
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Investigation of Drilled Cuttings Transport in Inclined Boreholes

Abstract: This paper describes an experimental investigation into drilled cuttings transport in inclined boreholes carried out in the Department of Petroleum Engineering at Heriot-Watt University.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
39
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 97 publications
(42 citation statements)
references
References 15 publications
3
39
0
Order By: Relevance
“…Gavignet and Sobey 6 also stated in their two-layer model that smaller particles need a higher flow rate to maintain bed motion. Ahmed However, Ford et al 10 observed that as the cuttings size decreases from 2.5-3.7 mm to 1.7-2.0 mm, the Minimum Transport Velocity (MTV) required both for cuttings rolling/sliding and for suspension decreases. It means that smaller cuttings are easier to transport in terms of MTV.…”
Section: Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…Gavignet and Sobey 6 also stated in their two-layer model that smaller particles need a higher flow rate to maintain bed motion. Ahmed However, Ford et al 10 observed that as the cuttings size decreases from 2.5-3.7 mm to 1.7-2.0 mm, the Minimum Transport Velocity (MTV) required both for cuttings rolling/sliding and for suspension decreases. It means that smaller cuttings are easier to transport in terms of MTV.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Though different cuttings have been tested by a few investigators, 4,5,7,8,[10][11][12] no study on small cuttings transport in horizontal or high angle annuli involving drill pipe rotation has been conducted. Previous conclusions about the cuttings size effects on cuttings transport are quite diverse, and even contradictory in some cases.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A number of experimental and modeling studies (Sifferman & Becker 1992;Brown 1986;Clark and Bickham 1994;Ford et al 1990) have been carried out to determine the effect of the angle of inclination. The studies indicate that the effect of inclination on cuttings transport is substantial.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Experimental studies have shown that hole cleaning is affected by many parameters, such as well geometry (diameter, inclination, eccentricity), cuttings characteristics (size, porosity of bed), drilling fluid properties (rheology, density, drag coefficient) and drilling operational parameters (drilling rate, drilling fluid circulation rate) (3)(4)(5)(6)(7) .…”
Section: Introductionmentioning
confidence: 99%